Influence of type of grinding parameters on roughness and tribological properties of combined metal-oxide-ceramic layers. - Похмурский, В.І.; Студент, М.М.; Шмирко, В.В.; Довгуник, В.М.; Клапків, М.Д. (Problems of Tribology, 2014)
Aluminum alloy scale use in industry taking pride of place on steel. However , they have a somewhat limited use in mobile pin pairs, because their relatively low surface hardness and wear resistance. To ensure continued operation of struc-tures and products of light alloys used modification of the surface layers or coatings applied to them . Perspective is com-bined metal-oxide-ceramic layers is applied to protect the solid aluminum alloys. To restore the geometric shape of worn parts we proposed to use electric arc spraying aluminum-based coatings, followed by oxidation sprayed layer.The article in-vestigates the structure and tribological characteristics of combined metal-oxide-ceramic layers synthesized on alloys and arc spraying aluminum-based coatings on various types of grinding.